A Field Data Analysis of Risk Factors Affecting the Injury Risks in Vehicle-To-Pedestrian Crashes - Zhang, Guanjun (Association for the Advancement of Automotive Medicine, 2008)
The head, torso, and lower extremity are the most commonly injured body regions during vehicle-to-pedestrian crashes. A total of 312 cases were selected from the National Automotive Sampling System (NASS) Pedestrian Crash Data Study (PCDS) database to investigate factors affecting the likelihood of sustaining MAIS 3+, AIS 3+ head, AIS 3+ torso, and AIS 2+ lower extremity injuries during vehicle-to-pedestrian frontal crashes. The inclusion criteria were pedestrians: (a) aged 14 years or older, (b) with a height of 1.5 m and taller, and (c) who were injured in an upright standing position via vehicle frontal collision. The injury odds ratios (ORs) calculated from logistic regression analyses were used to evaluate the association between selected injury predictors and the odds of sustaining pedestrian head, torso, and lower extremity injuries. These predictors included a crash factor (impact speed), pedestrian factors (age, gender, height, and weight), and vehicle factors (front bumper central height, front bumper lead, ground to front/top transition point height (FTTPH), and rear hood opening distance (RHOD)). Results showed that impact speed was a statistically significant predictor for head, torso, and lower extremity injury odds, as expected. Comparison of people 65 years of age and older to young adults aged 14 to 64 showed that age was also a significant predictor for torso (p<0.001, OR=23.8) and lower extremity (p=0.020, OR=2.44) injury odds, but not for head injuries (p=0.661). Vehicles with higher FTTPH and more vertical frontal structures were aggressive to pedestrians, especially regarding injuries to the torso. A very short RHOD would be more likely to lead the pedestrian to impact the windshield and windshield frame, thus increasing the head injury risk.